Pematahan Dormansi Benih Cabai Rawit Lokal (Capsicum frutescens L.) Asal Kecamatan Insana Tengah Kabupaten Timor Tengah Utara dengan Aplikasi Plant Growt Promoting Rhizobacteria - Ladianus Nahak (Fakultas Pertanian, Universitas Timor, 2021)
This study aims to determine the response of the seeds to the treatment used and the appropriate time of soaking the seeds for local cayenne pepper seeds. This research was carried out in August-September 2020 in the laboratory of the Faculty of Agriculture, Timor University, Sasi Village, Kefamenanu City District, TTU Regency. The design used in this study was a completely randomized design (RAK) with a factorial pattern. The first factor was the dose of PGPR which consisted of 3 treatments, namely without control PGPR, PGPR 25 g/5 L and PGPR 50 g/5 L. The second factor was the immersion time which consisted of 3 immersions namely 90 minutes immersion, 120 minutes immersion and 150 minutes immersion. There were 9 treatment combinations which were repeated 3 times so that in total there were 27 experimental units. The results showed that the response of local cayenne pepper seeds to the PGPR dose and immersion time showed no interaction but an interaction occurred in the parameter of Maximum Growth Potential. The treatment without PGPR (Control) gave the best results and was significantly different from the PGPR treatment on the vigor index observation parameter, the dry weight of normal sprouts while the other observation parameters were not significantly different. The treatment of PGPR soaking time for chili seeds was not significantly different except for the vigor index observation parameter with a soaking time of 90 minutes and the dry weight observation parameter of normal sprouts which was not significantly different from the soaking time of 120 minutes.